Dibenzo[b, d]furan/thiophene-fused double boron-based multiresonance emitters with narrowband ultrapure green electroluminescence. Issue 34 (11th April 2023) - Wang, Menglei; Fu, Zhangyi; Cheng, Rui; Du, Jiping; Wu, Tanping; Bin, Zhengyang; Wu, Di; Yang, Yudong; Lan, Jingbo
Abstract : Double boron-based multiresonance emitters DBF-DBN and DBT-DBN have been synthesized. The OLED device based on DBT-DBN shows an ultrapure green emission at 520 nm with EQEs up to 31.3% and a narrow FWHM of 24 nm. Abstract : Herein, double boron (DB)-based narrowband pure-green multiresonance (MR) emitters DBF-DBN and DBT-DBN have been designed and synthesized. Dibenzo[ b, d ]furan and dibenzo[ b, d ]thiophene as linkages between two B–N skeletons endow target DB-MR-emitters with a rigid and symmetric molecular structure, which efficiently extends the π-conjugation length and suppresses vibrational relaxation, resulting in a narrowband pure-green emission. DBT-DBN exhibits a remarkably higher reverse intersystem crossing (RISC) rate ( k RISC = 7.4 × 10 5 s −1 ) than DBF-DBN ( k RISC = 1.1 × 10 5 s −1 ) due to the heavy-atom effect of sulfur. The organic light-emitting diode (OLEDs) based on DBT-DBN shows an ultrapure green emission with maximum external quantum efficiencies (EQEs) up to 31.3%, an emission peak at 520 nm, and a narrow full-width at half-maximum (FWHM) of 24 nm, meeting the BT.2020 green standard.